Comparative mechanisms of acute high-alkalinity stress on the normal and hybrid populations of pacific white shrimp (Litopenaeus vannamei) - Ye, Yucong; Liu, Hang; Yuan, Haojuan; Du, Xinglin; Huang, Jiarong; Zhou, Yujie; Li, Yiming; Zhao, Yunlong (Frontiers in Marine Science, 2025)
In recent years, as anthropogenic activities the alkalinity of water bodies has intensified, which has seriously affected the development of aquaculture. Cross breeding can inherit the good traits of parents and develop stronger resistance to stress. Therefore, we investigated the advantages of the hybrid population (TH) of Litopenaeus vannamei over the normal variety (TC) in terms of survival rate, morphological changes of gill tissue, ion transport, and energy metabolism. After culture in the same environment, two species of shrimp were subjected to acute exposure to alkalinity levels of 50 mg/L, 200 mg/L, and 350 mg/L for 24 hours, and samples were taken at 0, 4, 8, 12, and 24 h, respectively. The study showed that under alkalinity stress, the TH group had a higher survival rate, greater hemolymph urea nitrogen content, and better gill tissue integrity compared to the TC group. The TH group also exhibited increased activities of key enzymes such as Na+/K+ ATPase and Ca2+/Mg2+ ATPase, along with elevated levels of urea nitrogen, arginase. Additionally, the expression of key genes, including NKA (Na+/K+-ATPase), CA (carbonic anhydrase), and HSPs (heat shock proteins) was upregulated in the TH group, that suggests that these genes may play a crucial role in improving tolerance to high-alkalinity environments. Our results demonstrated that under the same concentration of alkaline stress, the TH population had stronger nitrogen metabolism ability and stronger stress resistance than the TC population. This study can provide a theoretical reference for breeding high-alkalinity tolerance varieties of L. vannamei.